The administrative practices of some secondary school principals in the center of Nineveh Governorate and their role in the organizational loyalty of physical education teachers (College of Basic Education Research Journal, 2026)
The purpose of the research  was to identify the relationship and the percentage of contribution of administrative practices in its dimensions to the organizational loyalty of physical education teachers. The researchers used the  descriptive method and the survey method, and  the research population was selected and sampled by the deliberate comprehensive inventory method, where the research included physical education teachers in some secondary schools in the center of Nineveh province, which are (70) teachers. The researchers used two questionnaires, the first is a questionnaire administrative practices prepared by (Alayan, 2012), where the questionnaire consists of (42) paragraphs. The second is the  organizational loyalty   questionnaire prepared by (Manouba, 2013), where the questionnaire consisted of (17).The data were processed statistically using the favorable ratio, arithmetic mean, standard deviation, alpha coefficient, and linear regression coefficient using SPSS statistical program in data analysis0 and researcher One found that there is a relationship and a statistically  significant contribution ratio for administrative practices with their dimensions in  the organizational loyalty of physical education and sport sciences teachers at the University of Mosul.
Keywords: Management Practices; Organizational Loyalty